" ... [I]f I can [be] infected now that means I am going to die ... ": an explorative study focusing on vulnerable, immunocompromised groups and caregivers experiences and perceptions of the Covid-19 pandemic in South Africa - Alicia North; Allanise Cloete; Shandir Ramlagan; Thabang Manyaapelo; Amukelani Ngobeni; Noloyiso Vondo; Derrick Sekgala (Taylor & Francis Group, 2023)
ABSTRACTIn this paper, we explored how vulnerable, immunocompromised groups and caregivers of the elderly experienced and perceived the onset of the Covid-19 pandemic in South Africa. Semi-structured interviews were conducted remotely between the 5th andthe 18th of April 2020 in the three South African provinces hardest hit by Covid-19, namely Gauteng, KwaZulu-Natal and the Western Cape. In total, 60 qualitative key informant interviews and one focus group discussion were conducted. Study participants expressed concerns for elderly people and people with underlying health conditions because of their increased vulnerability to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). People living with HIV expressed an increased fear of infection following the advent of the Covid-19 pandemic in South Africa. The sidelining of healthcare services and stock-outs of medication proved to be an added concern in particular for vulnerable and immunocompromised groups. Overall, the data suggest that the fear of infection is ubiquitous for people who live in unstable environments such as overcrowded townships and informal settlements. Given the increased fears of infection brought on by the Covid-19 pandemic, the mental health of vulnerable communities and those caring for them becomes an added burden for people living in unstable environments.